THE DEVELOPMENT OF MARKETING IN TOURISM INDUSTRY - SOFRONOV, Bogdan (Annals of Spiru Haret University. Economic Series, 2019)
The purpose of this paper is how the marketing development and changing the tourism industry in the world. Tourism marketing is the business discipline of attracting visitors to a specific location. Hotels, cities, states, consumer attractions, convention centers and other sites and locations associated with consumer and business travel all apply basic marketing strategies to specific techniques designed to increase visits. In the tourism industry, marketing includes determining the unique selling benefit or benefits one area has over its competition. A destination might offer people looking to combine business and pleasure ease of travel to and from the area, ample convention halls and hotels, interesting nightlife, and activities for adult partners and children. The tourism marketing uses a wide variety of communications strategies and techniques to promote areas and destinations. A convention center might purchase advertisements in trade magazines for meeting planners and send direct mail materials to corporations that hold events. They might place ads in tennis or golf magazines to attract those consumers. The tourism destinations build websites and place ads in consumer publications read by their target customers. Chambers of commerce are involved in promoting their areas generally and the businesses within their areas specifically. This often includes offering potential visitors packets filled with brochures, discount coupons and other materials.